Determinants Of The Ability Of The Internal Compliance Unit To Detect Fraud With Professional Skepticism As A Moderator - Wahyuddin, Wahyuddin; Amiruddin, Amiruddin; Indrijawati, Aini (Jurnal Ekonomi, 2024)
This study aims to test and analyze the influence of competence, independence, and whistleblowing on the ability of internal compliance units to detect fraud, with professional skepticism as a moderation variable. This research was conducted in the Internal Compliance Unit of the Directorate General of Water Resources, the Directorate General of Highways, and the Directorate General of Cipta Karya. Primary data was collected through questionnaires and saturated sampling techniques, multiple regression analysis, and moderation regression analysis to test the research hypothesis. The study results show that competence, independence, and whistleblowing affect the ability of the internal compliance unit to detect fraud. Professional skepticism can moderate the influence of competence, autonomy, and whistleblowing on the ability of the internal compliance unit to detect fraud.